Application and Challenges of Digital Storytelling Based Artificial Intelligence for Language Skills: A Narrative Review - Tarigan, Fatin Nadifa; Hasibuan, Siti Aminah; Nurmayana (Association of Language Teachers in Southeast Asia (ALTSA), 2024)
Digital storytelling, coupled with Artificial Intelligence (AI), has emerged as a powerful tool for enhancing language skills in learners. This study explores the multifaceted applications of digital storytelling based AI in the realm of language education, shedding light on its pedagogical benefits and innovative possibilities. However, while the potential of AI digital storytelling is promising, it also presents several significant challenges. It critically examines the challenges and offer insights into its application for language classroom. The data were 12 journal publications studied searched on the Publish or Persih, Google Scholar and Scopus database and its publication time range is in 2020- 2023. By conducting narrative review, this study provides a comprehensive overview of the evolving intersection of technology and the benefits of AI- digital storytelling in language. education